A Simple Model of Banking Competition With Bank Size Heterogeneity and Lending Spillovers. (2nd April 2017) - Heddergott, Daniel; Laitenberger, Jörg
Abstract : We develop a multimarket spatial competition model in which large banks compete with small banks for transparent and opaque borrowers. Opaque borrower lending is influenced by a spillover from transparent borrower markets that depends on the structure of the banking market and is transmitted by banks' risk‐bearing capacities. Consistent with diverse empirical findings, the structure of the banking market determines whether competition improves credit access (small bank dominated markets) or reduces bank lending (large bank dominated markets). In sufficiently heterogeneous (homogeneous) banking markets, a U‐shaped (inverse U‐shaped) relationship between credit access and bank competition applies.